2021
DOI: 10.1021/acs.est.0c07413
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurements of Gas-Phase Trichloramine (NCl3) in an Indoor Aquatic Center

Abstract: NCl3 is formed as a disinfection byproduct in chlorinated swimming pools and can partition between the liquid and gas phases. Exposure to gas-phase NCl3 has been linked to asthma and can irritate the eyes and respiratory airways, thereby affecting the health and athletic performance of swimmers. This study involved an investigation of the spatiotemporal dynamics of gas-phase NCl3 in an aquatic center during a collegiate swim meet. Real-time (up to 1 Hz) measurements of gas-phase NCl3 were made via a novel on-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Subsequent surface disturbances in pool water, for example from swimming, have been shown to accelerate the transfer of produced chloraminespredominantly NCl 3to the gasphase. 10,11 Recent real-time measurements by Wu et al observed indoor NCl 3 levels increasing with the number of active swimmers, reaching peak concentrations up to 116 and 226 ppbv during swimming activities. 10 A median mixing ratio of 80 ppbv of NCl 3 was measured by Weng et al in an indoor swimming pool facility, despite a high outdoor to indoor air exchange rate (AER) of 9 h −1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent surface disturbances in pool water, for example from swimming, have been shown to accelerate the transfer of produced chloraminespredominantly NCl 3to the gasphase. 10,11 Recent real-time measurements by Wu et al observed indoor NCl 3 levels increasing with the number of active swimmers, reaching peak concentrations up to 116 and 226 ppbv during swimming activities. 10 A median mixing ratio of 80 ppbv of NCl 3 was measured by Weng et al in an indoor swimming pool facility, despite a high outdoor to indoor air exchange rate (AER) of 9 h −1 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recent real-time measurements by Wu et al observed indoor NCl 3 levels increasing with the number of active swimmers, reaching peak concentrations up to 116 and 226 ppbv during swimming activities. 10 A median mixing ratio of 80 ppbv of NCl 3 was measured by Weng et al in an indoor swimming pool facility, despite a high outdoor to indoor air exchange rate (AER) of 9 h −1 . 12 The observed high levels of NCl 3 highlights how even with proper ventilation chloramines can reach levels that are hazardous to human health indoors (see below).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term investigations of gas-phase NCl 3 concentration in indoor chlorinated swimming pools have been conducted in recent years [17][18][19][20]. However, most of these previous investigations have incorporated analytical methods that were only able to report measurements every 30 min or more [21]. In this study, gas-phase NCl 3 is measured with a Next Environmental Monitoring (NEMo) Indoor Air Quality (IAQ) monitor (NEMo XT, Ethera Labs, Crolles, France), which reports measurements of gas-phase NCl 3 concentration every 10 min [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The past thirty years have seen rapid advances in TCA exposure assessment, and several studies assessed TCA levels in indoor swimming pools using different sampling strategies (Soltermann et al, 2014;Zwiener and Schmalz, 2015;Wu et al, 2021). Modi ed Hery methods have been reported using different sampling pump ow rates and types of pre lters.…”
Section: Introductionmentioning
confidence: 99%